Long term exposure of saxitoxin induced cognitive deficits and YAP1 cytoplasmic retention - Shenpan Li; Xiao Chen; Qian Sun; Xiaohu Ren; Jiacheng Zhong; Li Zhou; Hongyu Zhang; Guowei Li; Yungang Liu; Jianjun Liu; Haiyan Huang (Ecotoxicology and Environmental Safety, 2023)
While most studies assessed the acute toxicity of saxitoxin (STX), fewer studies focus on the long-term degenerative effects of STX on the central nervous system. We investigated the cognitive impairment and hippocampal damages of 6 months’ exposure of low-dose STX to C57BL/6NJ mice with behavioral tests, H&E staining, and Western blots, and the possible mechanism (Ppp1C, YAP1, tau-phosphorylation) underlies the pathological changes. Furthermore, we discussed the specific localization of YAP1 in N2a cells induced by STX and the effect of inactivated Ppp1C on its downstream protein YAP1 in the Hippo signal pathway. We found STX intoxicated mice showed declined cognitive performance in both NOR test and MWM test, degenerations in the CA1 area of hippocampi. STX induced up-regulation expression of Ppp1C and YAP1 in hippocampus and N2a cells. Meanwhile, STX treatment induced cell apoptosis and Tau protein hyperphosphorylation. In addition, STX treatment promoted YAP1 cytoplasmic retention that indicates the activation of Hippo pathway, while depletion of Ppp1C inactivate YAP1 during the treatment of STX. Our results highlight the role of Ppp1C and YAP1 cytoplasmic retention in chronic low-dose STX intoxication.